Solely sutures is a reliable fixation for valgus-impacted proximal humeral fractures - Scheer, Johan H. (J Clin Orthop Trauma, 2020)
PURPOSE: Valgus impacted proximal humeral fractures with substantial displacement may severely compromise shoulder function and open reduction can therefore be considered. Internal fixation hardware may eventually however constitute problems. In a small subset of these fractures, in which there is no medial comminution and intact blood supply it is possible to use a least possible fixation method with solely sutures through the tendons of the rotator cuff and the shaft as described by Bigliani 1990. The aim of the present study was to investigate the outcome of this fixation method in a retrospective series of patients. METHODS: Twenty-seven patients, 23 women and 4 men, with a mean age of 66 years (53–83) and minimum follow-up time of 2 years (2–11 years) accepted follow-up with standard shoulder radiographs and 22 were examined with Oxford Shoulder Score (OSS), Constant-Murley (CM) shoulder score and Numeric Rating Scale for pain (NRS). Reoperations or adverse events were recorded. RESULTS: The median OSS was 45 (range 5–48) and CM 63 (range 21–98). The relative CM score was 81% of the uninjured side and median NRS 0 (range 0–5). No reoperations were undertaken. One patient had a complete avascular necrosis (AVN), 3 patients had a partial AVN of the humeral head and two a partial resorption of the greater tuberosity. CONCLUSION: The use of sutures only for fixation of displaced valgus-impacted proximal humeral fractures provided a relatively reliable outcome with good functional scores and no reoperations. There appears to be no need for the use of hardware for fixation of this rare subset of fractures.